1992
DOI: 10.1073/pnas.89.14.6423
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a DNA repair gene (XRCC5) involved in double-strand-break rejoining to human chromosome 2.

Abstract: Complementation of the repair defect in hamster xrs mutants has been achieved by transfer of human chromosome 2 using the method of microcell-mediated chromosome transfer. The xrs mutants belong to ionizing radiation complementation group 5, are highly sensitive to ionizing radiation, and have an impaired ability to rejoin radiation-induced DNA double-strand breaks. Both phenotypes were corrected by chromosome 2, although the correction of radiation sensitivity was only partial. Complementation was achieved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Importantly, human p86Ku colocalizes with xrs, another XRCC5 mutant (23). xrs cells are restored for IRS and V(D)J recombination defects by microcell-mediated transfer of human chromosome 2 (15,33). During the publication of this work, the repair and recombination defects of xrs-6 cells were shown to be complemented by p86Ku (34).…”
Section: Discussionmentioning
confidence: 86%
“…Importantly, human p86Ku colocalizes with xrs, another XRCC5 mutant (23). xrs cells are restored for IRS and V(D)J recombination defects by microcell-mediated transfer of human chromosome 2 (15,33). During the publication of this work, the repair and recombination defects of xrs-6 cells were shown to be complemented by p86Ku (34).…”
Section: Discussionmentioning
confidence: 86%
“…However, poly(ADP-ribose) polymerase has a much higher affinity for heat-denatured calf thymus DNA than for untreated DNA (32), making it clearly distinct from DEB factor. Furthermore, the gene maps to human chromosome 1 (9), while chromosome 2 restores X-ray resistance and V(D)J recombination to group 5 cells (19,43).…”
Section: Resultsmentioning
confidence: 99%
“…The XRCC5 gene has been mapped to 2q35, the same region as that of the Ku86 gene (6,16,21). In addition, group 5 cells lack a DNA-end-binding (DEB) activity with an abundance, nuclear localization, DNA substrate specificities, and antigenic determinants similar to those of Ku (13,36,37).…”
mentioning
confidence: 99%
“…First, human Ku86 cDNA did not completely rescue group 5 mutants. Second, chromosome mapping experiments sampled only a fraction of the human genome (6,21) and therefore failed to rule out the possibility that complementing activity was present on another chromosome in addition to chromosome 2. Therefore, we in-troduced a wild-type hamster cDNA into group 5 mutant cells and demonstrated that this could completely restore DEB activity, Ku70 protein levels, X-ray resistance, and V(D)J recombination.…”
mentioning
confidence: 99%